2012
DOI: 10.1016/j.ijpddr.2011.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Parasite neuropeptide biology: Seeding rational drug target selection?

Abstract: The rationale for identifying drug targets within helminth neuromuscular signalling systems is based on the premise that adequate nerve and muscle function is essential for many of the key behavioural determinants of helminth parasitism, including sensory perception/host location, invasion, locomotion/orientation, attachment, feeding and reproduction. This premise is validated by the tendency of current anthelmintics to act on classical neurotransmitter-gated ion channels present on helminth nerve and/or muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 251 publications
0
47
0
Order By: Relevance
“…One approach to novel drug target discovery in nematodes is the interrogation of alternative, unexploited , facets of this already proven repository (see [3] for review). Within the neuropeptidergic system, motor functions (reproduction, feeding and locomotion) are known to be modulated by FMRFamide-like peptides (FLPs); the nematode FLPergic system remains unexploited for parasite control (see [3][9] for review). The potential of FLPergic signalling as a control target resource embedded within nematode neuromuscular functionality has been highlighted [3].…”
Section: Introductionmentioning
confidence: 99%
“…One approach to novel drug target discovery in nematodes is the interrogation of alternative, unexploited , facets of this already proven repository (see [3] for review). Within the neuropeptidergic system, motor functions (reproduction, feeding and locomotion) are known to be modulated by FMRFamide-like peptides (FLPs); the nematode FLPergic system remains unexploited for parasite control (see [3][9] for review). The potential of FLPergic signalling as a control target resource embedded within nematode neuromuscular functionality has been highlighted [3].…”
Section: Introductionmentioning
confidence: 99%
“…One application of com parative genomic analysis has already revealed that the ge netic bases of developmental arrest in C. elegans and H. glycines differ significantly (Elling et al, 2007), provid ing important guidance for analysis of development. The area of nematode neuropeptides and their application for nematode control has flourished with a foundation in C. elegans genetics (Li, 2005;Li & Kim, 2010) and the co operation amongst those investigating the genetics, phys iology and biochemistry of these regulatory molecules in free-living, plant-parasitic and animal-parasitic nema todes (McVeigh et al, 2008(McVeigh et al, ,2012Holden-Dye & Walker, 2011;Maule & Curtis, 2011;Atkinson et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Platyhelminthes appear to lack a conventional endocrine system [38], and are therefore heavily reliant on neural signalling via neuropeptides that control vital dynamic physiological and neural functions, such as growth, reproduction, host-seeking olfaction, locomotion, immune evasion and sexual dimorphism [61]. The importance of their peptidergic neural and associated receptor systems holds a promising area of research for new anthelmintic drug targets [16, 62, 63]. …”
Section: Discussionmentioning
confidence: 99%
“…G-protein coupled receptors (GPCRs) are the largest family of receptors found in eukaryotes, with more than 40 % of all pharmaceuticals targeting their various subfamilies [15]. Due to the large diversity and expansion of GPCRs between species and their ability to respond to a large selection of ligands, selectivity for GPCR-targeted anthelmintic drugs is very promising [16, 17]. GPCRs are integral membrane receptors, and respond to a multitude of extracellular ligands to transduce and amplify (or inhibit) intracellular responses involved in metabolism, neuromuscular regulation, endocrine function, vision and olfaction [15].…”
Section: Introductionmentioning
confidence: 99%